Perbandingan Defisit Neurologis Pada Pasien Stroke Berdasarkan Letak Lesi Pada Hemisfer: Literature Review - Ovilia Nabila; Dwi Kartika Rukmi (Jurnal Keperawatan Notokusumo, 2021)
Background: Stroke is one of the vascular injuries with the highest incidence in theworld. Stroke can cause neurological deficits in the form of disturbances in movement,sensation, cognitive function, and emotions that are mild or severe depending on thelocation of the damage, how large the area is experiencing inadequate perfusion, anddepending on the function of the damaged area. Objective: To compare neurologicaldeficits in stroke patients based on the location of the lesions in the hemisphere.Methods: We conducted a systematic literature review on articles published in the2011-2021 period. Data was collected from three databases (Google Scholar, PubMed,and Portal Garuda), using the keywords “Neurologic Deficit”,“Stroke”,“Hemisphere”. Results: 10 articles were included in the review. The results obtained:(1) The incidence of decreased cognitive function is more common in left hemisphericstroke patients, (2) Unilateral neglection is more common in right hemispheric strokepatients. (3) there is no difference between balance and level of ability to perform dailyactivities. (4) the incidence of post-stroke depression is suspected to be higher inpatients with left hemisphere lesion stroke and is one of the causes of decreased qualityof life in post-stroke patients. Conclusion: Specialization of hemispheric functionaffects the severity of neurological deficits in stroke patients.